The relationship between clinical audit and ethics - Kinn, S. (Journal of medical ethics, 1997)
The aim of this paper is to start a debate about ethical issues associated with the practice of clinical audit. This is an area that has not received much consideration. The role of clinical audit is to raise general clinical standards. The ethical issues of clinical audit may have far-reaching consequences for clinicians, patients, health care providers and purchasers. Guidance is required to provide consistency in approach so that those involved in clinical audit, at whatever level, can be confident that they are following good practice. Clinicians and managers often think of good practice as being a technical matter. The main point of this paper is to bring out important ethical dimensions to good practice.